Effective adaptation of flight muscles to tebuconazole-induced oxidative stress in honey bees - Máté Mackei; Fanni Huber; Csilla Sebők; Júlia Vörösházi; Patrik Tráj; Rege Anna Márton; Zsuzsanna Neogrády; Gábor Mátis (Heliyon)
The widespread and excessive agricultural use of azole fungicide tebuconazole poses a major threat to pollinator species including honey bee colonies as highlighted by recent studies. This issue is of growing importance, due to the intensification of modern agriculture and the increasing amount of the applied chemicals, serving as a major and recent problem from both an ecotoxicological and an agricultural point of view. The present study aims to detect the effects of acute sublethal tebuconazole exposure focusing on the redox homeostasis of honey bee flight muscles. The results show that the redox homeostasis, especially the glutathione system, of the exposed animals is severely impaired by the treatment, but flight muscles are able to successfully counteract the detrimental effects by the effective activation of protective processes. This efficient adaptation may have led to overcompensation processes eventually resulting in lower hydrogen peroxide and malondialdehyde concentrations after exposure. It could also be assumed that tebuconazole has a non-monotonic dose-response curve similarly to many other substances with endocrine-disrupting activity concerning parameters such as superoxide dismutase activity or total antioxidant capacity. These findings shed light on the detrimental impact of tebuconazole on the redox balance of honey bee flight muscles, also highlighting, that unlike other organs such as the brain, they may effectively adapt to acute tebuconazole exposure.